Impact of Organizational Factors on Deviant Workplace Behavior in Pakistani Public Organizations: The Moderating Role of Transformational Leadership (Journal of Business Management and Accounting, 2017)
The present study examined the impact of organizational factors on deviant workplace behavior and the moderating role of transformational leadership in managing the impact of organizational factors on deviant workplace behavior (DWB) and, drawing on the theoretical supports of social exchange theory, social learning theory and the psychological contract theory. A total of 380 individuals from 20 public organizations situated in Lahore, the Punjabi provincial capital of Pakistan, participated in the present study. The results from Structural Equation Modeling are presented using SPSS and AMOS. The results revealed significant relationship and supported the hypothesized direct impact of organizational factors on deviant workplace behavior in Pakistani public organizations. However, moderating effect of transformational leadership among organizational factors and deviant workplace is not supported as hypothesed.